Aplikasi Pemesanan Makanan di Restoran menggunakan Program Langganan berbasis Android - Fanny Fanny (IJNMT (International Journal of New Media Technology), 2020)
The purpose of this research is to make an application that give an information to the waiter or waitress about the table that want to ask for help and to chef or drink maker about the order sequentially, to easily make the restaurant management to renew the menu list without pay for more surcharge, ease the customer to save their point and for increase customer’s loyalty, help the customer to count their individual payment including the tax, and to ease the restaurant to analyze the revenue, product, and customer satisfaction. The method of this research is collecting data (interview), analysis method, system design method (use case diagram, activity diagram, class diagram, sequence diagram, application interface, and incremental SDLC), and also literature review. The result is mobile application based on android for food ordering and web application for restaurant management. The conclusion of this application is this application ”TMS Cafe” help restaurant to increase the customer loyalty using membership system, ease customer to store their point, simplify the restaurant to manage the menu and promo list with digital system, facilitate the restaurant to give information to customer about the active promo, ease customer to order food, increase the customer satisfaction with song request feature, facilitate customer to count their individual payment including taxes and also to see the transaction and point usage history.